2010
DOI: 10.1097/icl.0b013e3181d13a90
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Vision Correction and Lens Tolerance in Keratoconus Patients Prescribed a Contact Lens With Dual Aspherical Curves

Abstract: Fitting of an Aphex KC lens improved visual acuity and increased lens wear time in keratoconus patients who were intolerant of a spherical RGP contact lens. Aphex KC thus provides a viable alternative for management of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…A multitude of lenses has been developed for patients with this condition [8][9][10][11][12][13][14][15][16][17][18][19]. However, no previous study has examined a bevel toric lens, designed to improve bevel width and tear exchange efficacy, in such patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A multitude of lenses has been developed for patients with this condition [8][9][10][11][12][13][14][15][16][17][18][19]. However, no previous study has examined a bevel toric lens, designed to improve bevel width and tear exchange efficacy, in such patients.…”
Section: Discussionmentioning
confidence: 96%
“…Individuals with keratoconus in the advanced stage require a rigid gas-permeable (RGP) contact lens to reduce distortion and provide better vision [7][8][9]. Fitting of an RGP lens improves visual acuity, and many such lenses have been developed for management of keratoconus patients [8][9][10][11][12][13][14][15][16][17][18][19]. However, RGP lenses can cause discomfort as a result of their small bevel width, which is necessitated by the difference in radius of curvature of the cornea between the vertical and horizontal directions in advanced keratoconus [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on aspherical-curve HCLs have been reported by Yanai et al [ 16 ] and Kazanci et al [ 17 ]. In the report by Yanai et al, the E value of the peripheral-zone curve design was small, and HCLs were not used for severe cases [ 16 ]. In this study, aspherical-curve HCLs were used for stages 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…Yanai ve ark. 13 çalışmalarında gözlükle görme keskinliğini 0,70 logMAR (20/111), kontakt lensle görme keskinliğini 0,20 logMAR (20/29) bulmuşlardır. Fatima ve ark.…”
Section: Discussionunclassified